VD_FINDINFO ML / 2009 / 72 vom 23. April 2009 - VD Tribunal cantonal (2009)
MAINLEVÉE DÉFINITIVE, RECONNAISSANCE DE LA DÉCISION, CONVENTION{SIGNIFICATION ET NOTIFICATION DES ACTES JUDICIAIRES} | 27 ch. 2 CL, 80 LP, 81 al. 1 LP